Recruitment in a Monopsonistic Labour Market: Will Travel Costs be reimbursed? - Jan Rouwendal; Jos van Ommeren (Tinbergen Institute, 2007)
Reimbursement of commuting costs by employers has attracted little attention from economists. We develop a theoretical model of a monopsonistic employer who determines an optimal recruitment policy in a spatial labour market with search frictions and show that partial reimbursement of commuting cost will in general be an element of the recruitment policy. The empirical evidence we offer is consistent with the interpretation of reimbursement as the result of monopsonistic behaviour. The alternative explanation that stresses the role of tax incentives is unlikely to provide a full explanation of the commuting costs reimbursement.
Keywords: J33; 330; monopsonistic labour markets; commuting; spatial labour market analysis; Pendelverkehr; Kosten; Personalbeschaffung; Arbeitsmarkt; Monopson; Raumwirtschaftstheorie